Grey matter volume and thickness abnormalities in young people with a history of childhood abuse. Issue 6 (10th November 2017) - Lim, L.; Hart, H.; Mehta, M.; Worker, A.; Simmons, A.; Mirza, K.; Rubia, K.
Abstract : Background: Childhood abuse is associated with abnormalities in brain structure and function. Few studies have investigated abuse-related brain abnormalities in medication-naïve, drug-free youth that also controlled for psychiatric comorbidities by inclusion of a psychiatric control group, which is crucial to disentangle the effects of abuse from those associated with the psychiatric conditions. Methods: Cortical volume (CV), cortical thickness (CT) and surface area (SA) were measured in 22 age- and gender-matched medication-naïve youth (aged 13–20) exposed to childhood abuse, 19 psychiatric controls matched for psychiatric diagnoses and 27 healthy controls. Both region-of-interest (ROI) and whole-brain analyses were conducted. Results: For the ROI analysis, the childhood abuse group compared with healthy controls only, had significantly reduced CV in bilateral cerebellum and reduced CT in left insula and right lateral orbitofrontal cortex (OFC). At the whole-brain level, relative to healthy controls, the childhood abuse group showed significantly reduced CV in left lingual, pericalcarine, precuneus and superior parietal gyri, and reduced CT in left pre-/postcentral and paracentral regions, which furthermore correlated with greater abuse severity. They also had increased CV in left inferior and middle temporal gyri relative to healthy controls. Abnormalities in the precuneus, temporal and precentral regions were abuse-specific relative to psychiatric controls, albeit at a more lenient level. Groups did not differ in SA. Conclusions: Childhood abuse is associated with widespread structural abnormalities in OFC–insular, cerebellar, occipital, parietal and temporal regions, which likely underlie the abnormal affective, motivational and cognitive functions typically observed in this population.